PEMBERDAYAAN KELOMPOK IBU PKK MELALUI PELATIHAN OLAHAN PANGAN LIDAH BUAYA DENGAN METODE PARTICIPATORY RURAL APPRAISAL - D. Nurhaida; I. Busnetty; T.T.H. Tambunan; M.A. Munawar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This community service activity was given to a women’s group in RT 007 RW 13 Sukadanau Village, West Cikarang District, Bekasi, West Java. This activity aims to provide training and assistance in processing aloe vera into processed food products that have economic value. This activity is a collaboration between the Faculty of Economics and Business, Trisakti University, and PT. Coca-Cola Europacific Partners Indonesia, together with village officials and the local community. The methods used are